2006
DOI: 10.1007/s10310-006-0203-1
|View full text |Cite
|
Sign up to set email alerts
|

An improved transformation system for Lombardy poplar (Populus nigravar.italica)

Abstract: We report an improved transformation system for Lombardy poplar (Populus nigra var. italica). A new binary vector, pBF2, with 11 unique restriction enzyme sites and the normal neomycin phosphotransferase II (NPTII) gene was constructed for the transformation of Lombardy poplar. Genetically transformed adventitious shoots were directly regenerated after cocultivation of stem segments with Agrobacterium tumefaciens EHA105 that harbored a binary vector with genes for the NPTII and enhanced green fluorescent prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…In agreement with a report [11], we found that a combination of 0.5 mg/L IBA and 0.02 mg/L NAA was the most effective dose for root development in Lombardy poplar (Figure 1(C) and 1(D)), although 0.5 mg/L IBA alone could induce roots in 50% of the regenerated shoots ( Table 2). Doubling the concentration of IBA and NAA in the medium did not improve the root induction efficiency ( Table 2).…”
Section: Root Inductionsupporting
confidence: 80%
See 3 more Smart Citations
“…In agreement with a report [11], we found that a combination of 0.5 mg/L IBA and 0.02 mg/L NAA was the most effective dose for root development in Lombardy poplar (Figure 1(C) and 1(D)), although 0.5 mg/L IBA alone could induce roots in 50% of the regenerated shoots ( Table 2). Doubling the concentration of IBA and NAA in the medium did not improve the root induction efficiency ( Table 2).…”
Section: Root Inductionsupporting
confidence: 80%
“…Then, four weeks old calli developed in CIM were repeatedly subcultured in SIM containing 2 mg/L trans-zeatin and 0.2 mg/L benzylaminopurine (BA), followed by re-transfer to root induction medium (RIM). In later by Nishiguchi et al [11], much simple regeneration method had been developed for Lombardy poplar regeneration, without callus formation. But, still they relied on pre incubation of explants in CIM (0.5 mg/L 2,4-D and 1 mg/L BA) for 6 days.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, transformation protocols have been developed for P. alba (Okumura et al, 2006), P. tremula (Fladung et al, 1997;Tzfira et al, 1997), P. tremuloides (Cseke et al, 2007), P. tremula × P. alba (Leple et al, 1992), P. tremula × P. tremuloides (Fladung et al, 1997), Populus canescens × P. grandidentada and P. tremuloides × P. davidiana (Dai et al, 2003). Successful transformation have been reported for species and hybrids from sections Aigeiros (cottonwood) and Tacamahaca (balsam poplar) including P. deltoides, P. trichocarpa "Nisqually-1" Song et al, 2006), P. trichocarpa × P. deltoides (De Block, 1990;Han et al, 2000), P. deltoides × P. nigra (Heuchelin et al, 1997), P. alba × P. grandidentata (Fillatti et al, 1987) and P. nigra × P. trichocarpa (McCown et al, 1991), P. sieboldii × P. grandidentata (Matsunaga et al, 2002), P. nigra "Italica" (Nishiguchi et al, 2006) and P. ciliata (Thakur et al, 2005). The most widely used transformation "laboratory rat," has been the Populus tremula × alba hybrid clone known as INRA 717-1B4 (Leple et al, 1992).…”
Section: Transformation Methods In Populusmentioning
confidence: 99%